Analysis of accelerometer signals in human physical activities - Li, Hao (БНТУ, 2023)
This paper examines accelerometer signals related to physical activity. It involves a meticulous analysis of acquired data during the preprocessing stage and utilizes a range of indicators to determine the most suitable data management parameters. This data analysis plays a pivotal role in preprocessing human sensor data, as selecting appropriate parameters can significantly enhance the accuracy of activity prediction.